Utilizing Greimas Semiotic Square in the Analysis of Binarism in Some Selected Fables of ’Kalila wa Dimna’ - Al-Hassan Al-Hiloo, Zainab Alaa Abd; Al-Hussein Al-Mosawi, Fatima Raheem Abd; Amer Al-Jarry, Ala' Dhafer (International Journal of English Literature and Social Sciences (IJELS), 2019)
'Kalila wa Dimna' fables are tales which include short tales revolving around two human-characterized animals which are often in opposition. This opposition gives rise to the existence of a binary implying two contrasting concepts ascribed to these two animals. (positive and negative terms), which in turn are linked to further semiotic relationships constituting the oppositional binary. To arrive at the meaning of a binary, it must be analyzed to show how the fable's meaning is constructed. The most workable model is that of Greimas' Semiotic Square which can be utilized to distinguish the types of opposition involved and to explore the types of the relationship underlying the oppositional relationship constituting the fable's binary. Two fables of 'Kalila wa Dimna' have been selected to be analyzed in terms of Greimas' square The study concludes that the two animals in Aesop's Fables generally represent two opposing terms (positive and negative) which are semiotically further analyzed into two implicit relationships (contradiction and implication). In other words, the componential meaning of a binary is based on the interrelations between these contrasting terms.